2013
DOI: 10.1063/1.4797464
|View full text |Cite
|
Sign up to set email alerts
|

Full-dimensional quantum calculations of the vibrational states of ${\rm H}_5^+$H5+

Abstract: Full-dimensional quantum calculations of the vibrational states of H5(+) have been performed on the accurate potential energy surface developed by Xie et al. [J. Chem. Phys. 122, 224307 (2005)]. The zero point energies of H5(+), H4D(+), D4H(+), and D5(+) and their ground-state geometries are presented and compared with earlier theoretical results. The first 10 low-lying excited states of H5(+) are assigned to the fundamental, overtone, and combination of the H2-H3(+) stretch, the shared proton hopping and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 62 publications
3
34
0
Order By: Relevance
“…We also compare our results to those obtained from multiconfigurational time-dependent Hartree (MCTDH) calculations, 31 vibrational configuration interaction (VCI) calculations obtained using the reaction path version of MULTIMODE, 32 and full CI (FCI) calculations. 33 We believe that the 33 cm −1 shift in the zero-point energy calculated using the basis set DMC approach reflects an incomplete treatment of the coupling between the torsion and the other vibrational degrees of freedom. In particular, this approach neglects couplings between the torsion and displacements of the central proton from the vector that connects the centers of mass of the outer H 2 units, R ⃗ in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…We also compare our results to those obtained from multiconfigurational time-dependent Hartree (MCTDH) calculations, 31 vibrational configuration interaction (VCI) calculations obtained using the reaction path version of MULTIMODE, 32 and full CI (FCI) calculations. 33 We believe that the 33 cm −1 shift in the zero-point energy calculated using the basis set DMC approach reflects an incomplete treatment of the coupling between the torsion and the other vibrational degrees of freedom. In particular, this approach neglects couplings between the torsion and displacements of the central proton from the vector that connects the centers of mass of the outer H 2 units, R ⃗ in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…These reduced-dimensional Hamiltonians replace the full-dimensional (12D) rovibrational Hamiltonian and are used to provide physical insight into the motions of the atoms of H + 5 . The vibrational and rovibrational levels of H + 5 have been computed both by variational nuclear motion [29,30,32,33] and diffusion Monte Carlo (DMC) [31,34,35] techniques. The full-and reduced-dimensional variational computations performed by three of the present authors [18] utilised the GENIUSH algorithm and code [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The proton delocalization is reflected in the low frequency of this vibrational mode as has been seen in both experimental and a variety of theoretical studies of the vibrational spectrum of H + 5 . 11,[13][14][15][16][17][18][19][20] In a recent study, we demonstrated that this proton hopping vibration is strongly coupled to the dissociation coordinate in H + 5 . 14 The third process is more complicated than the first two.…”
Section: Introductionmentioning
confidence: 87%
“…This choice of coordinates has been employed in many of the studies on H + 5 of Prosmiti and co-workers 16,17,19,20 as well as by Fàbri et al 34 In the second set of Jacobi coordinates, the dissociation coordinate S is defined as the vector that connects H 2 and H + 3 , and the remaining coordinates are designated by s i . Such coordinates were used by Song et al 18 and provide a more appropriate description of H + 5 as it dissociates. It should be noted that, as they are defined in Fig.…”
Section: A Minimized Energy Path Diffusion Monte Carlomentioning
confidence: 99%